Interactive Augmented Reality Media within the Contextual Flipped Group Classroom Model to Foster Students' Science and Social Learning Motivation - Nasrah Nasrah; Syarifah Aeni Rahman; Fitri Yanty Muchtar; Ummu Khaltsum; M. Takdir; Muh. Takbir; Sri Mahardini Putri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2026)
The advancement of educational technology presents significant opportunities for creating more interactive, contextual, and motivating learning experiences for students. However, Natural and Social Sciences (IPAS) instruction in elementary schools is still frequently conducted through conventional methods that fail to encourage active student participation and learning motivation. This study aims to develop and examine the effectiveness of innovative interactive learning media based on Augmented Reality (AR) integrated within the Contextual Flipped Group Classroom (CFGC) model to enhance elementary students' motivation in learning IPAS. This research employs a Research and Development (R&D) approach utilizing the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The research subjects consisted of 224 elementary school students divided into experimental and control groups. The research instrument comprised a learning motivation questionnaire encompassing five indicators: achievement goals, performance goals, learning value, active learning strategies, and self-efficacy. Data analysis was conducted using Analysis of Covariance (ANCOVA) and independent t-tests. The findings demonstrate that the implementation of AR-based interactive media within the CFGC model significantly enhanced students' IPAS learning motivation across all motivational dimensions (p < 0.05). The highest improvement was observed in the self-efficacy and active learning strategies dimensions, indicating that AR media effectively cultivates students' confidence and active engagement in learning IPAS concepts. These findings confirm that the integration of AR-based interactive media within the CFGC model represents an effective pedagogical innovation for fostering elementary students' IPAS learning motivation. This media provides more contextual, collaborative, and meaningful learning experiences, thereby strengthening the implementation of 21st-century digital technology-based learning.